2023
DOI: 10.1021/acs.analchem.2c04643
|View full text |Cite
|
Sign up to set email alerts
|

DNAzyme-Based Microscale Thermophoresis Sensor

Abstract: Microscale thermophoresis (MST) technology has emerged as a powerful growing method in a molecular interaction study by measuring fluorescence responses of molecules inside a capillary to infrared (IR) laser heating with the benefits of rapid ratiometric measurement, separation-free, no immobilization, and low sample consumption. Combining the advantages of RNA-cleaving DNAzymes in target recognition and enzymatic catalysis and the strength of MST technology for fluorescence signaling, here, we reported a DNAz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The intrinsic properties of molecules, including their size, charge, and hydration shell, determine their thermophoretic movements. , In general, when the binding of aptamers to target proteins occurs, the above-mentioned properties of aptamers change and thus alter their movement . Information on aptamer–protein interactions can be obtained by monitoring the distribution and intensity changes in fluorescence signals of fluorescent dye-labeled aptamers. , …”
Section: Detection Methods Of Aptamer–protein Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intrinsic properties of molecules, including their size, charge, and hydration shell, determine their thermophoretic movements. , In general, when the binding of aptamers to target proteins occurs, the above-mentioned properties of aptamers change and thus alter their movement . Information on aptamer–protein interactions can be obtained by monitoring the distribution and intensity changes in fluorescence signals of fluorescent dye-labeled aptamers. , …”
Section: Detection Methods Of Aptamer–protein Interactionsmentioning
confidence: 99%
“…306 Information on aptamer−protein interactions can be obtained by monitoring the distribution and intensity changes in fluorescence signals of fluorescent dye-labeled aptamers. 307,308 QCM is a microgravimetric sensing strategy for determining aptamer−protein interactions. 309−311 Utilizing the piezoelectric effect of quartz crystals, QCM converts the surface mass change of the quartz crystal electrode into frequency shift of the quartz crystal resonator.…”
Section: Other Assaysmentioning
confidence: 99%
“…MST offers the potential to evaluate turnover rates of enzymatic reactions, especially in cases in which no direct detection via uorescence reporter exists. 38,39 Therefore, we sought to determine the intrinsic difference of the substrate's m 6 A modication in thermophoresis behaviour. For this purpose, we simulated different m 6 A methylation levels from 0-100% by mixing the synthetic substrate oligo with its methylated analogue at a total RNA concentration of 100 nM (Fig.…”
Section: Development Of An Mst-based Mettl3/14 Enzyme Assaymentioning
confidence: 99%
“…TRIC reflects fluorescence response of the fluorophores to heating, which is governed by the intrinsic property of fluorophores, local environment of fluorophores, and conformation of fluorescently labeled molecules . Studies have shown that TRIC can be the main contributor for MST signal. , Compared with other methods for the molecular interaction study, MST has strengths in trace sample consumption, free separation, free immobilization, high throughput, easy sample handling, high speed, and ratiometric analysis. MST can analyze various types of biomolecular interactions, such as protein–protein interactions, nucleic acid–protein interactions, small molecule–protein interactions, etc. , Specially, MST is not only useful in molecular interaction studies but also promising for target quantification. , …”
mentioning
confidence: 99%